Determinant of Long-Term Contraceptive Method Use Among Married Women of Reproductive Age: Cross-Sectional Study in Urban Area of South Sumatra - Haerawati Idris; Indah Purnama Sari; Nining Ade Ningsih (Jurnal Ilmu Kesehatan Masyarakat, 2025)
The Sustainable Development Goals (SDGs) emphasize the integration of reproductive health into national strategies and programs, including universal access to sexual and reproductive health services such as Family Planning (FP). This study aims to examine the factors influencing the use of long-term contraceptive methods among married women of reproductive age in urban areas of South Sumatra. A quantitative approach with a cross-sectional design was employed, using secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS). The sample consisted of 247 married women. Data were analyzed using logistic regression. In urban areas of South Sumatra, 13.8% of married women of reproductive age used long-term contraceptive methods. The use of these methods was significantly associated with the number of living children and employment status (p < 0.05). Among all variables, education was found to be the most strongly associated factor with the use of long-term contraceptive methods (p = 0.04; PR = 4.238, 95% CI: 1.070–16.779). Education plays a pivotal role in the use of long-term contraceptive methods. Enhancing knowledge and awareness about these methods significantly influences women’s decisions to adopt them.